An Examination of Search Methodologies of Meta-Analyses in Peer-Reviewed Articles Related to Crop Science. - Bradley Brazzeal (Issues in Science and Technology Librarianship)
The value of meta-analysis is becoming more recognized by agricultural researchers, and an important component of a proper meta-analysis is a comprehensive search of the relevant literature. This study examines the search methodologies of 140 crop science-related meta-analyses published in peer-reviewed journals. Specific information sought included databases searched, the use of reference list browsing to find additional studies, search string details, listing of publications used in the meta-analysis, and inclusion of non-journal publications. It was found that researchers often do not seem to have a good grasp on how to sufficiently document their search methodology in a way that allows for replication, and in some cases they may not be aware of how to conduct an effective, comprehensive search. The results highlight the need for researchers conducting a meta-analysis or similar project to collaborate with librarians who have expertise in literature searching. [ABSTRACT FROM AUTHOR]